A Comparative Study on the Design of a Two-Story Car Showroom Using Pre-Engineered Buildings (PEBs) in Accordance with British Standards and Euro Codes - Balamuralikrishnan R.; Mohammedali, Ibrahim Shabbir (Engineering Research: Perspectives on Recent Advances Vol. 5, 2025)
Steel has been used as a construction material for a very long time. Most steel structures are used for low-rise, single-story industrial buildings. Steel is preferred for these buildings due to its higher strength-to-weight ratio compared to reinforced concrete (RCC), and because it allows for larger, unobstructed internal spaces with long clear spans between columns. Pre-engineered buildings (PEBs) represent a modern approach to structural steel utilization, optimizing design for economical structural integrity. Structural members are designed and fabricated in a controlled factory environment to produce optimal sections by varying member thickness along their length according to bending moment requirements. The PEB concept utilizes the amount of steel required and produces the most optimum sections based on the bending moment requirement. The actual model of the PEB structure of the car showroom was created in STAAD Pro software. This research paper analyzes and designs a two-story (G+1) PEB car showroom using STAAD.Pro, in accordance with British Standards (BS 5950-1:2000) and Euro codes (EC3 EN-1993-1), including wind and seismic analysis. To achieve this, two models of the car showroom were created in STAAD.Pro: a British Standard (BS) model and a Euro code (EC) model. The BS model used tapered frame sections, while the EC model used universal standard section frames. Both models were analyzed under dead load, live load, wind load, and seismic load. Wind and seismic loads, being critical dynamic loads, were analyzed to assess structural stability against lateral forces. The analysis and design results for both models were within allowable limits for ultimate and serviceability limit states, as the internal stresses in all members satisfied the unity check ratio requirements for both design codes. Dynamic analysis suggests that the EC model exhibits higher seismic resistance compared to the BS model, as the maximum displacement in the X-direction was 8.83 mm for the EC model and 10.5 mm for the BS model. The total structural weight was 1125.431 kN for the BS model and 1214.315 kN for the EC model, making the EC model 7.9% heavier. Furthermore, the total weight of all portal frames was 457.26 kN for the BS model and 574.725 kN for the EC model, indicating that the tapered frame sections in the BS model reduced steel usage by 25.7%. Therefore, the BS model proved more economical compared to the Euro code model. In order to determine the most cost-effective method of designing the PEB car showroom using British standard and Euro code, it is crucial to compare the design results of the two models and identify the structure that would be durable and economical in terms of material used.